2022
DOI: 10.1063/5.0104889
|View full text |Cite
|
Sign up to set email alerts
|

Full-dimensional automated potential energy surface development and dynamics for the OH + C2H6 reaction

Abstract: We develop a full-dimensional analytical potential energy surface (PES) for the OH + C2H6 reaction using the Robosurfer program system, which automatically (1) selects geometries from quasi-classical trajectories, (2) performs ab initio computations using a CCSD(T)-F12/triple-zeta-quality composite method, (3) fits the energies utilizing the permutationally-invariant monomial symmetrization approach, and iteratively improves the PES via steps (1)−(3). Quasi-classical trajectory simulations on the new PES revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 48 publications
1
28
0
2
Order By: Relevance
“…Excitation of the CH stretching modes (ν 1 , ν 5 , and ν 7 ) clearly increases the reaction probabilities, again in accordance with the ICSs. As we have recently discussed in our previous work, the scattering angle distributions are connected to the shape of these opacity functions. At the lowest collision energy, the probabilities show a monotonic decrease with increasing impact parameter until approximately b = 4 and then the curves rapidly drop off.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…Excitation of the CH stretching modes (ν 1 , ν 5 , and ν 7 ) clearly increases the reaction probabilities, again in accordance with the ICSs. As we have recently discussed in our previous work, the scattering angle distributions are connected to the shape of these opacity functions. At the lowest collision energy, the probabilities show a monotonic decrease with increasing impact parameter until approximately b = 4 and then the curves rapidly drop off.…”
Section: Resultsmentioning
confidence: 69%
“…In the same year, we also started to investigate the title reaction using high-level ab initio methods such as CCSD­(T)-F12b, CCSDT­(Q), and MRCI showing that, besides the H 2 O + C 2 H 5 channel, hydrogen- and methyl-substitution can also occur at higher collision energies resulting in the H + C 2 H 5 OH and CH 3 + CH 3 OH products, respectively . Based on the benchmark ab initio characterization of the stationary points of the multichannel OH + C 2 H 6 reaction, in 2022 we developed a full-dimensional coupled-cluster-quality analytical PES, which allowed efficient dynamics investigations using the quasi-classical trajectory (QCT) method . The dynamics simulations for the ground-state OH­(ν = 0) + C 2 H 6 (ν = 0) reaction showed that the reactivity of the hydrogen- and methyl-substitution channels is negligible besides hydrogen abstraction in the collision energy range of 10–50 kcal/mol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those for the 1-propanol reaction, in which we detect abstraction at both α- and β-sites, are much more broadly scattered. Recently, Czakó and co-workers have reported a classical trajectory study of the OH + ethane reaction over a broad collision energy range . They also reported large vibrational excitation in the H 2 O product, and a shift from rebound dynamics to stripping dynamics as the collision energy is increased from 10 to 50 kcal mol –1 .…”
Section: Discussionmentioning
confidence: 99%
“…Apart from methane, ethane is the most commonly adopted hydrocarbon, and numerous studies have been performed involving various reactions, such as C( 1 D) + C 2 H 6 , 9 C 2 H + C 2 H 6 , 10 N( 2 D) + C 2 H 6 , 11 Mu + C 2 H 6 , 12 C 4 H + C 2 H 6 , 13 H + C 2 H 6 , 14 F + C 2 H 6 , 15,16 Cl + C 2 H 6 , 17,18 Br + C 2 H 6 , 19 I + C2H6, 20 O + C 2 H 6 , 21 and OH + C 2 H 6 . 22,23 In particular, most of these reactions possess van der Waals wells in the reactant and product valleys, and the depth of the wells varies with the reactions. [24][25][26][27] Considering that the depth the of van der Waals well may have a critical impact on the reaction rate constant, three different reactions (i.e.…”
Section: Introductionmentioning
confidence: 99%